Linkage between pain sensitivity and empathic response in adolescents with autism spectrum conditions and conduct disorder symptoms. Issue 2 (16th June 2016) - Chen, Chenyi; Hung, An‐Yi; Fan, Yang‐Teng; Tan, Shuai; Hong, Hua; Cheng, Yawei
Abstract : Lack of empathy is one of the behavioral hallmarks in individuals with autism spectrum conditions (ASC) as well as youth with conduct disorder symptoms (CDS). Previous research has reliably documented considerable overlap between the perception of others' pain and first‐hand experience of pain. However, the linkage between empathy for pain and sensitivity to physical pain needs to be empirically determined, particularly in individuals with empathy deficits. This study measured the pressure pain threshold, which indexes sensitization of peripheral nociceptors, and assessed subjective ratings of unpleasantness and pain intensity in response to empathy‐eliciting stimuli depicting physical bodily injuries in three age‐ and sex‐matched participant groups: ASC, CDS, and typically developing controls (TDC). The results indicated that the pain threshold was lowest in the ASC group and highest in the CDS group. The ASC group displayed lower ratings of unpleasantness and pain intensity than did the TDC and CDS groups. Within the ASC and CDS, pain intensity ratings were significantly correlated with unpleasantness ratings to others' pain. Moreover, the ASC significantly differed from the TDC in the correlation between pain threshold values and unpleasantness ratings. These findings may cast some light on the linkage between atypical low‐level sensory functioning, for instance altered pain sensitivity, and high‐level empathic processing. Autism Res 2017, 10: 267–275 . © 2016 International Society for Autism Research, Wiley Periodicals, Inc.